Less is more? Think again! A cognitive fluency-based more-less asymmetry in comparative communication. [article]. - Hoorens, Vera; Bruckmuller, Susanne
Differences between groups, individuals, or objects can be framed in multiple ways. One can, for instance, say that men generally earn more than women or that women generally earn less than men. Showing that these logically equivalent expressions are not psychologically equivalent, we demonstrate a robust more-less asymmetry in the use of and responses to comparative statements. More specifically, we show that people use "more than" statements more often than "less than" statements (Study 1); like "more than" statements better (Studies 2 and 3), agree more with opinions expressed through "more than" statements (Studies 4 and 5), and are more likely to consider factual "more than" statements to be true (Study 6). Supporting a cognitive fluency explanation, a manipulation that makes people expect disfluency while processing "less than" statements reduces this otherwise robust more-less asymmetry (Study 7). By combining comparative framing effects with cognitive fluency, the present research brings together 2 research fields in social cognition, shedding new light on both.-- (from the authors)